Usage of Fruit-Infused Water for Prevention of Dehydration Due to Endurance Exercise - Ali, Mohammad Arif; Rahayu, Setya; Indardi, Nanang; Anggita, Gustiana Mega; Soraya, Fatona; Rustadi, Tri; Wicaksono, Anggit; Chen, Yu Shiuan; Chang, Yun Zhen (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
This study aimed to extend previous investigation regarding its beneficial effects on changes of blood glucose. This experimental research was conducted from 06:00-12:00. Twenty-four young men (age 19-20 y.o.) were divided into three groups, Fasting-Exercise-Only (FEO), Fasting-Exercise-Water (FEW), and Fasting-Exercise with Fruit-Infused Water (FEF). Subjects underwent fasting for 12 h before the experimental day. The data of body weight (Kg) and macroscopic urine color were collected before and after exercise. Body weight in all experimental groups were decreased by 1% during endurance exercise. There were no differences in decrease of body weight between FEF and FEW groups compared to FEO group (p>.05). The change in urine color was significantly different between pre-exercise and post-exercise data (p<.05). The darkest urine color was observed in FEO group (4.75), followed by FEW group (4.25), while FEF group (3.63) did not reach dehydration level. In conclusion, fruit-infused water is suggested to be drink as a choice for fluid intake during exercise.